(untitled) (Global Journal of Science Frontier Research, 2023)
The general fragmented state of modern Science could not but affect virology which lost its upper sense and dug into numerous scattered experimental data Therefore a general analysis of both the description definition of the virus itself and its position in the interval between Inanimate Nature and LIFE was required At the same time in order to build the phenomenology of viruses it is necessary to take into account the modern provisions of related sciences